Necrotising sarcoid granulomatosis. A rare granulomatous disease - Doubkova, Martina; Hausnerová, Jitka; Výška, Ondřej; Richter, Svatopluk; Merta, Zdeněk (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Introduction: Necrotizing sarcoid granulomatosis (NSG) is a very rare disease of unknown etiology characterized by sarcoid-like granulomas, vasculitis and necrosis in pulmonary and extrapulmonary localizations. Case report: We describe a case of a 34-year-old Caucasian male with fever, pleural pain, and nodular pulmonary opacities on chest radiograph. Histological examination of the lung tissue confirmed NSG. Diagnostically, infectious causes, vasculitis, and malignancy were excluded. A tendency to partial regression was observed, without the need for corticosteroid treatment. Conclusion: NSG is a rare disease which must be distinguished from other systemic diseases including vasculitides. The key to diagnosis, emphasized in our paper, is the histopathological finding. The course of NSG is similar to sarcoidosis. Corticosteroids are considered the treatment of choice, but the disease exhibits a tendency towards spontaneous regression.